2013
DOI: 10.1136/annrheumdis-2013-203323
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption as a preventive factor for developing rheumatoid arthritis: a dose-response meta-analysis of prospective studies

Abstract: Low to moderate alcohol consumption inversely associated with the development of RA in a manner that appears to be dose-dependent, time-dependent and sex-dependent. Large prospective studies that investigate gene-environment interactions are required to further clarify the aetiology of RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 31 publications
2
76
1
5
Order By: Relevance
“…This is inconsistent with recently published meta-analyses [11,12]. One reason to this discrepancy could be that the consumption of alcohol in these patients and controls was lower than in studies showing associations [20,21] and may, therefore, mask a significant association due to a lack of individuals reaching critical levels for the protective effect of alcohol.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…This is inconsistent with recently published meta-analyses [11,12]. One reason to this discrepancy could be that the consumption of alcohol in these patients and controls was lower than in studies showing associations [20,21] and may, therefore, mask a significant association due to a lack of individuals reaching critical levels for the protective effect of alcohol.…”
Section: Discussioncontrasting
confidence: 71%
“…Although studies have suggested associations, mainly regarding fruit, vegetables, meat and disease development, the results have been inconclusive [4][5][6][7][8][9][10]. Regarding the consumption of alcohol, recently published meta-analyses concluded that moderate consumption of alcohol intake is inversely associated with the development of RA [11,12].…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, in multiple epidemiologic studies and including studies where data regarding alcohol intake was collected prior to incident RA, modest alcohol consumption (in some studies 1–2 drinks daily) has been associated with decreased risk for RA (97–101), although not invariably (98). There have also been mixed results of the protective effect of alcohol in longitudinal studies of individuals who have presented to clinical care with musculoskeletal symptoms in absence of IA on examination at baseline.…”
Section: Environmental Risk Factors For Ramentioning
confidence: 99%
“…First, a major limitation of our meta-analysis of observational studies was the possibility of uncontrolled confounding. Although major potential confounders had been adjusted for in most included studies, residual or unknown confounding cannot be excluded (Aune et al, 2011;Jin et al, 2013). For instance, the exposure potential in underground miners has been described as complex, with multiple carcinogenic occupational exposures.…”
Section: Limitations Of the Meta-analysismentioning
confidence: 98%